Intrinsic capacity and its association with predictors among Chinese empty nest older adults in communities: a latent class analysis - Wenxin Guo; Lina Meng; Junzhe Han; Bin Yang; Jiayu Sun; Yuting Guo; Jiawei Wu; Yang Liu (BMC Geriatrics)
Abstract Objectives This study aimed to examine Intrinsic Capacity (IC) subgroups and the association of IC subgroups with IC predictors in Chinese urban empty nesters. Methods A convenient sample of 385 older adults aged 60 and above in Community Health Service Center was recruited from Hei Longjiang Province, China, between June 2023 and December 2023. Latent class Analysis (LCA) was conducted to explore IC subgroups using the sensory, cognition, locomotion, psychological, and vitality domains of IC as input variables. Multinomial logistic regression was performed to explore the association between latent subgroups and the IC predictors. Results We identified three IC subgroups: "Low IC level—Low locomotion domain"(33.5%), "Medium IC level—Low sensory domain" (16.9%) and "High IC level" (49.6%). Being young, married, without multimorbidity, receiving visits from children ≥ 1 time per week, a low score of self-neglect, a high score of social networking, and a low score of loneliness were closely correlated to the "High IC level" subgroup of empty-nest older adults in communities. Conclusion The potential subgroups of the IC of empty-nest older adults in communities can be identified through five IC domains. The older empty-nesters should pay extra attention to their critical IC predictors. Community medical staff and other workers should provide intervention measures for different subgroups of older adults to improve their IC in an effective and individualized manner.